(3GdJhLjg Gdegfj aj GdeDSSGJ GdUfGYjI (B/s - (3ehSi, aJMj eMeOs ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2012)
(3eONd Edi Yde GdfaS h NUGFUg, CgOGag h aQhYg, GdJhLjg h GdGNJjGQ Gdegfj, GdJCgjd Gdegfj dGUMGH GdGYGbI, GdJOQjH Gdegfj, OQGSI GdaQO h WQb gPg GdOQGSI h CNjQG JMdjd GdGYeGd GdegfjIs
Keywords: (3GdJOQjH Gdegfjs; (3GdJYdje GdUfGYjs; (3GdeDSSGJ GdUfGYjIs